The Containment of Organised Crime and Terrorism : Thirty-Five Years of Research on Police, Judicial and Administrative Cooperation. - Fijnaut, Cyrille J. C. F. (BRILL, 2016)
This unique volume collects articles and contributions to edited books published throughout his distinguished career by Professor Cyrille Fijnaut, one of the world's leading experts in the fields of organised crime, security and criminology. It makes clear what issues the author systematically explored over the years and how he helped to shape the fields in which he has worked, and continues to work. The texts, reflecting the author's profound understanding of these complex fields and wealth of experience on a practical level, are presented according to topic. In addition, the volume offers English translations of seminal articles published originally in Dutch, thus making these important texts accessible to international scholars for the first time. The volume thus constitutes a unique and indispensable resource for scholars and practitioners, inside and outside the Netherlands.